Engineering properties of normal and high strength concrete containing palm oil clinker / Fuad Y. M. Abutaha - Fuad Y. M. , Abutaha (2018)
Utilization of locally available waste materials to replace conventional concrete materials has gained considerable attention in the past two decades. Palm oil clinker (POC) is a lightweight waste material generated from the palm oil industry in Malaysia. POC, when crushed possesses the potential as aggregates for concrete production. Experimental investigation on the usage of POC as a partial and full replacement of the natural aggregates and filler material was carried out in this study. Normal and high strength concrete of 40 and 90 MPa respectively, were the design strength for the purpose of this study. Department of environment (DOE) and Sherbrooke mix design methods were adopted to produce the normal and high strength concrete, respectively. Crushed POC was partially and fully used to replace natural aggregates i.e. fine and coarse. The percentage of POC replacement used are 0%, 20%, 40%, 60%, 80% and 100% of the total volume of fine and coarse aggregate, separately. Particle-packing (PP) method was then adopted for the mixes where coarse aggregate was substituted with POC. To enhance the engineering properties of POC concrete, addition of Palm oil clinker powder (POCP) was then incorporated to the mixes as a filler material to fill up the voids of POC, while maintaining the other mix constituents. Fresh and hardened properties were investigated for the concrete mixes with and without POCP and the results were compared to the control concrete, which was prepared using natural aggregates. POC, being highly porous had a negative effect on the fresh and hardened concrete properties when coarse aggregate was substituted with POC. Meanwhile, the replacement of the natural sand with POC fine had insignificant effect on fresh and hardened properties of concrete. The results also revealed that incorporating additional POCP to normal and high strength POC concrete improved the engineering properties as well as the durability performance. Therefore, there is a great potential towards utilization of POC in the normal concrete production. This approach offers an environmental friendly solution to the ongoing challenge of palm oil mill waste materials.